Laparotomic intrauterine insemination with frozen-thawed semen in Sopravissana breed ewes in Central Italy. Issue 1 (1st January 2021) - Sylla, Lakamy; Pistolesi, Alessia; Corsi, Ivan; Crociati, Martina; Stradaioli, Giuseppe; Monaci, Maurizio
Abstract: Intrauterine laparoscopic insemination is diffuse in sheep breeding, yet requires veterinary expertise and expensive equipment. Our aim was to evaluate the time required, reproductive outcome and post-operative complications of mini invasive laparotomic intrauterine insemination, as an alternative approach to laparoscopy. A total of 115 Sopravvissana breed ewes were enrolled, including 75 adults and 40 lamb ewes, after oestrus synchronisation. Ewes were sedated and restrained in dorsal recumbence. Uterine horns were exposed through an abdominal incision of 4–7 cm, cranially to the udder. Thawed semen, containing 100 × 10 6 progressive motile (70%) and morphologically normal (80%) sperm cells, was inoculated into uterine lumen through an intravenous catheter. The abdominal incision was then routinely closed. The time interval for: (a) laparotomy and uterine exteriorisation, (b) intrauterine insemination, (c) abdominal wall closure and (d) total procedure was recorded. Pregnancy, lambing, twinning rates and sex ratio were submitted to chi-square test, comparing lamb and adult ewes. Time intervals and the duration of laparotomic procedure were compared in lamb and adults through Mann–Whitney U test for independent samples. Median ± standard error (SE) of total time for laparotomic intrauterine insemination was 5.53 ± 0.07 and 4.99 ± 0.11 min, for adult and lamb ewes ( p <.05), which was similar to what was reported for laparoscopic methods. At pregnancy check, 60% and 70% of adult and lamb ewes resulted pregnant. Laparotomy is poorly applied due to risk of adherence and decreased fertility. In our study, ewes were naturally bred in the following season with 90% pregnancy rate. Our results showed that time for laparotomy is quite similar to laparoscopic insemination, as for the conception and lambing rates. HIGHLIGHTS: Time required for the overall procedure (5.53 ± 0.07 and 4.99 ± 0.11 min, for adult and lamb ewes, respectively, with significant difference ( p <.05)) was similar to laparoscopic artificial insemination. About 60% and 70% of adult and lamb ewes resulted pregnant, respectively. No decreased fertility was observed in the following breeding season (90% pregnancy rate at natural insemination). Laparotomic approach is quite similar to laparoscopic insemination, in terms of time required for its complete achievement, for the conception and lambing rates; furthermore it has the advantage of reducing equipment costs.